Effective heat transfers in packed bed: Experimental and model investigation. (29th June 2019) - Zenner, A.; Fiaty, K.; Bellière-Baca, V.; Rocha, C.; Gauthier, G.; Edouard, D.
Highlights: We propose a new method for estimated the key parameters involved in packed bed. Its robustness has been proved and the results are compared at the literature. It allows designing optimal shapes for heat transfer and pressure drop in packed bed. Abstract: In industry, many heterogeneous solid/gas reactions are exothermic. Consequently, the radial heat transfer properties can be an important key for the process optimization. In this context, thermal tests were conducted in an innovative laboratory pilot. Radial temperature profiles are measured between a central hot-wire and the cooling jacket of the tube. Two models were presented in order to estimate the heat transfer coefficients from the experimental data. The results are discussed and compared with the main literature correlations. The influence of the particle shapes on heat transfers and the pressure drop is investigated.